Evaluation of commercial Pacific white shrimp Litopenaeus vannamei (Boone, 1931) feeds: growth performance and body carcass analysis - Rheido, Gestar; Novriadi, Romi; Suhardi, Muhammad Tegar Alif; Suharyadi, Suharyadi; Sektiana, Sinar Pagi; Margono, Margono; Mulyono, Mugi (Journal Omni-Akuatika, 2022)
Growth performance, survival rate, productivity, and carcass analysis were examined in the whole grow-out production system for Pacific white shrimp Litopenaeus vannamei fed four commercial diets over 15 weeks. Shrimp were held in twelve hapas nets with a size of 2 x 2 x 1 m and installed within the commercial ponds. The shrimp were stocked with the density of 100 shrimp m-2 per net in a completely randomized design (CRD). All feed used in this study was characterized with high protein levels within the range of 40 – 42% labeled as HP A and B; and medium protein levels (30 – 35%), labeled as MP A and B. Based on the proximate and nutritional profile analysis of the diet, the nutritional profile of HP B, MP A and MP B written on the feed bags showed an inconsistent results compared to the results of the test.  Shrimp fed the highest protein level had higher final body weight; feed conversion ratio, thermal growth coefficient, survival rate and average daily growth compared to MP B. Shrimp fed higher protein level also exhibited the lowest feed conversion ratio compared to the group of shrimp fed with medium protein. The results obtained in this study indicated that with small difference in growth rates, especially between HP groups compared with MP A, there is still a chance to re-formulate the diet to produce a cost-effective diet that still fulfill the specific nutrient requirement of the shrimp. Feed did not influence the nutritional deposition of the whole body of shrimp, but it seemed due to the inappropriate drying techniques Keywords: Protein level, growth, carcass, Litopenaeus vannamei, specific nutrient